The Role of Instructional Scaffolding in Enhancing Learner Autonomy Based on the Philosophy of Pragmatic Education: A Systematic Literature Review : Peran Scaffolding Pembelajaran dalam Meningkatkan Otonomi Peserta Didik Berdasarkan Filsafat Pendidikan Pragmatis: Systematic Literature Review - Fawziah Zahrawati B; Rukiyati (Bestari: Jurnal Pendidikan dan Kebudayaan, 2026)
This study synthesizes the role of instructional scaffolding in enhancing learner autonomy grounded in pragmatic educational philosophy through a Systematic Literature Review. It examines scaffolding characteristics, models, and mechanisms; the conceptualization and operationalization of learner autonomy; and the integration of pragmatic educational principles in existing scholarship. Following the PRISMA 2020 framework, the review draws primarily on Scopus (2015–2025) and one additional source, yielding 31 studies analyzed through thematic-comparative synthesis. Findings show that scaffolding is commonly implemented through modeling, guided practice, structured reflection, cognitive load management, and the gradual release of support. Learner autonomy is operationalized through indicators such as self-regulation, metacognition, intrinsic motivation, self-efficacy, and learning responsibility. Pragmatic principles, particularly experiential learning, contextual adaptation, and reflective practice, consistently emerge across studies. The review concludes that instructional scaffolding serves as a strategic mediating mechanism in fostering the transition from dependence to autonomous learning within an integrated conceptual framework.